Boronic acid-functionalized iron oxide magnetic nanoparticles via distillation–precipitation polymerization and thiol–yne click chemistry for the enrichment of glycoproteins. (1st October 2018) - Bi, Changfen; Zhang, Sitong; Li, Yiliang; He, Xiwen; Chen, Langxing; Zhang, Yukui
Abstract : Synthesis of phenylboronic acid functionalized iron oxide nanoparticles for glycoprotein enrichment via distillation–precipitation polymerization combined with thiol–yne click chemistry. Abstract : In this work, a novel strategy is developed for the fabrication of phenylboronic acid functionalized iron oxide magnetic nanoparticles (MNPs) via distillation–precipitation polymerization and thiol–yne click chemistry. Firstly, silica was coated on the Fe3 O4 MNPs using a sol–gel method to obtain Fe3 O4 @SiO2 . Subsequently, the vinyl groups were grated onto the silica-modified Fe3 O4 surface using 3-methacryloyloxypropyltrimethoxysilane. Next, alkynyl groups as the clickable sites were modified on the MNPs to obtain the product Fe3 O4 @pPMA via distillation–precipitation polymerization of the vinyl end groups with propargyl methacrylate, ethylene glycol dimethacrylate. Finally, phenylboronic acid was grafted on the surface of Fe3 O4 @pPMA via thiol–yne click chemistry. The morphology, structure, and composition of all the synthesized phenylboronic acid functionalized Fe3 O4 MNPs (Fe3 O4 @pPMA-MPBA) were characterized by transmission electron microscopy (TEM), Fourier transform infrared (FT-IR) spectroscopy, X-ray powder diffraction (XRD), vibrating sample magnetometry (VSM), X-ray photoelectron spectroscopy (XPS) and thermogravimetric analysis (TGA). Three glycoproteins ovalbumin, transferrin, and horseradish peroxidase and two non-glycoproteins lysozyme and horse heart cytochrome are the chosen target proteins and their adsorption performance on Fe3 O4 @pPMA-MPBA is investigated. The Fe3 O4 @pPMA-MPBA MNPs exhibited outstanding advantages towards glycoproteins including high adsorption capacity, excellent specificity, repeatability and good enrichment recovery. Furthermore, the Fe3 O4 @pPMA-MPBA MNPs could efficiently enrich glycoproteins from real egg white samples. This study provides a feasible strategy for the surface functionalization of boronate affinity nanomaterials for the selective isolation and enrichment of glycoproteins.